WATER SCARCITY AND INTERSTATE COOPERATION DYNAMICS IN NARYN/SYR DARYA RIVER BASIN - KAYUMOV, Abdurasul (CENTRAL ASIA AND THE CAUCASUS, 2012)
The Syr Darya River (together with the Naryn River) has a length of 3,019 km and its basin is a part of the Aral Sea basin, making it one of the most important transboundary rivers in Central Asia. The river is formed in Kyrgyzstan and flows through Tajikistan, Uzbekistan, and Kazakhstan. The flow of the Syr Darya River and its tributaries are regulated by a series of reservoirs built during the Soviet and post-Soviet periods. The most important among them is the Toktogul reservoir, with a 19.5 cubic kilometer water storage capacity. Toktogul, constructed in the 1970s, is currently located in Kyrgyzstan. The reservoir area is approximately 280 square kilometers and is capable of regulating the flow of the Syr Darya River. The riparian countries of the Syr Darya basin have been experiencing intense conflicts over water distribution since the disintegration of the Soviet Union. While the upstream countries constantly face a shortage of energy resources in the winter seasons, the downstream countries have to struggle with water shortages in the summer. The states in the upper reach intend to use water from Toktogul for electricity generation, whereas countries in the lower reach want to operate the reservoir for irrigation. The final consensus over the reservoir operation mode has not been achieved so far. On the contrary, it generates frequent tensions between the upstream and downstream countries. Moreover, environmental degradation, climate change, and population growth can lead to additional tensions over regional water sharing, which may increase the likelihood of violent conflict in Central Asia.